PENINGKATAN KETERAMPILAN MENULIS TEKS BIOGRAFI MENGGUNAKAN MODEL INVESTIGASI KELOMPOK DENGAN PEMANFAATAN MEDIA FOTO PADA SISWA KELAS X SMKN 3 BANDUNG - Fri Sisca Ulandari; Panca Pertiwi Hidayati; Adi Rustandi (STKIP Subang, 2023)
This research is motivated by the low ability of students in writing biographical texts. One of the factors that causes this is the lack of use of effective and innovative learning models by educators. Of the many learning models, the group investigation model can be used as an alternative for learning to write biographical texts. The purpose of this research was to find out the skills of students in writing biographical texts by applying the group investigation model. The approach used in this research is a quantitative approach. The results of this study will discuss the data that has been collected from the subjects and objects of research, the results of data processing, as well as the analysis of data processing. The author compiled the results of this study after conducting research on class X students of SMKN 3 Bandung, including class X AKL I as the experimental class and class X AKL II as the control class. The average result of the experimental pre-test was 75.69 which experienced an increase in the average post-test result to 85.22 while the average result of the control pre-test was 57.03 which experienced an increase in the post-test average result to 70.06. It can be concluded that both the experimental class and the control class experienced an average increase in the results of student scores. Based on the results of the output of the Mann Whitney test above, it is known that the post-test results for the experimental and control classes obtained the Mann Whitney test value of 0.00 <0.05, so the hypothesis is accepted. Based on these results the researcher concluded that by using the investigative model this group was able to help students in writing biographical texts.